Cartilage defect repair in a rat model via a nanocomposite hydrogel loaded with melatonin-loaded gelatin nanofibers and menstrual blood stem cells: an in vitro and in vivo study - Libo Yuan; Ling Yao; Xianzhen Ren; Xusheng Chen; Xu Li; Yongqing Xu; Tao Jin (Journal of Materials Science: Materials in Medicine)
Abstract Cartilage damage caused by injuries or degenerative diseases remains a major challenge in the field of regenerative medicine. In this study, we developed a composite hydrogel system for the delivery of melatonin and menstrual blood stem cells (MenSCs) to treat a rat model of cartilage defect. The composite delivery system was produced by incorporation of melatonin into the gelatin fibers and dispersing these fibers into calcium alginate hydrogels. Various characterization methods including cell viability assay, microstructure studies, degradation rate measurement, drug release, anti-inflammatory assay, and radical scavenging assay were used to characterize the hydrogel system. MenSCs were encapsulated within the nanocomposite hydrogel and implanted into a rat model of full-thickness cartilage defect. A 1.3 mm diameter drilled in the femoral trochlea and used for the in vivo study. Results showed that the healing potential of nanocomposite hydrogels containing melatonin and MenSCs was significantly higher than polymer-only hydrogels. Our study introduces a novel composite hydrogel system, combining melatonin and MenSCs, demonstrating enhanced cartilage repair efficacy, offering a promising avenue for regenerative medicine. Graphical Abstract